2017
DOI: 10.4314/tjpr.v16i6.27
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous determination of ten compounds in two main medicinal plant parts of Tibetan herb, <i>Pterocephalus hookeri</i> (CB Clarke) Höeck, by ultra-high performance liquid chromatography-photodiode array

et al.

Abstract: Purpose: To develop an ultra-high performance liquid chromatography (UPLC) -photodiode array (PDA)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Currently, it was considered that iridoids were the main anti-inflammatory constituents in this herb [ 6 ]. Sweroside, isolated and identified from P. hookeri [ 7 ], was a typical iridoid that exhibits diverse biological activities, such as hepatoprotective [ 8 ], antidiabetic [ 9 ] and anti-inflammatory [ 10 ] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, it was considered that iridoids were the main anti-inflammatory constituents in this herb [ 6 ]. Sweroside, isolated and identified from P. hookeri [ 7 ], was a typical iridoid that exhibits diverse biological activities, such as hepatoprotective [ 8 ], antidiabetic [ 9 ] and anti-inflammatory [ 10 ] effects.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have confirmed that the major chemical components of P. hookeri include iridoid glycosides, triterpenoid saponins, and phenolic acids [5,6]. A survey of ancient literature revealed that P. hookeri was frequently used in the treatment of RA [7].…”
Section: Introductionmentioning
confidence: 99%